2002
DOI: 10.1111/0162-895x.00295
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Terrorism: Disentangling the Effects of Personal and National Threat

Abstract: The events of 11 September 2001 have led to a higher perceived risk of terrorism in the United States. A better understanding of the political consequences of 9/11 requires a more complete accounting of the nature and consequences of perceived threat. Here, the distinction between perceived personal and national risks is examined in terms of two competing hypotheses: (1) The personal threat of terrorism has a pervasive influence even on national decisions and perceptions, in line with its highly arousing natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
269
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(297 citation statements)
references
References 46 publications
19
269
2
7
Order By: Relevance
“…Denne forskningen, som hovedsakelig er basert på en amerikansk kontekst, har som nevnt vist at terrorfrykt styrker gruppetilhørigheten til grupper som er lik en selv, mens befolkningen blir mer fiendtlig innstilt overfor grupper de oppfatter som annerledes (Sunstein 2004;Huddy, Feldman, Capelos & Provost 2002;Huddy et al 2005;Huddy & Feldman 2011). Med andre ord: gruppetenkningen forsterkes i fryktpregede situasjoner.…”
Section: Kjernen I Denneunclassified
See 1 more Smart Citation
“…Denne forskningen, som hovedsakelig er basert på en amerikansk kontekst, har som nevnt vist at terrorfrykt styrker gruppetilhørigheten til grupper som er lik en selv, mens befolkningen blir mer fiendtlig innstilt overfor grupper de oppfatter som annerledes (Sunstein 2004;Huddy, Feldman, Capelos & Provost 2002;Huddy et al 2005;Huddy & Feldman 2011). Med andre ord: gruppetenkningen forsterkes i fryktpregede situasjoner.…”
Section: Kjernen I Denneunclassified
“…I analysen undersøkes en rekke kjennetegn ved innbyggerne som litteraturen har pekt på som viktige i undersøkelsen av holdninger til antiterrorpolitikk og terrorfrykt (Huddy Grupper Forskjeller ( al. 2002;Lerner, Gonzales, Small & Fishhof 2003;Gadarian 2010;Albertson & Gadarian 2015).…”
Section: Empirisk Analyse Ii: Betyr Det Noe Hvem Innbyggerne Er?unclassified
“…The feel of fear and insecurity generated after the accident can be translated into a personal threat by each individual and then will influence their behavior. This presumption of personal threat will make every individual take a measures to minimize their exposure to risk and motivate them to take action to reduce the risk [4]. This change on personal behavior of each individual, will make a great change on how the society behave.…”
Section: Effects Of the Generated Fear And Its Correlation With Sociamentioning
confidence: 99%
“…A number of studies have shown that there is a strong relationship between threat perceptions and public opinion (Arian 1989;Huddy et al 2002Huddy et al , 2005. Terrorist threat perceptions, public opinion and support for public policy are often linked to underlying factors such as high media exposure, global experience and political knowledge (Ridout, Grosse and Appleton 2008).…”
Section: Terrorism and Political Preferencesmentioning
confidence: 99%